Clinical Management of an Unusual Case of Gingival Enlargement (Mustansiria Dental Journal, 2018)
The purpose of this article is to report a case of conditioned gingival enlargement managed by non surgical periodontal therapy. Hormones are specific regulatory molecules that modulate a host of body functions. Hormonal effects reflect physiologic and pathologic changes in almost all tissues of the body with the periodontium being no exception. Physiologic changes like puberty, the menstrual cycle, and pregnancy cause hormonal variations that may cause inflammation of the gingiva. Oral contraceptives that contain estrogen and/or progesterone are associated with gingival enlargement.A 28-year-old female presented with a complaint of swelling of the gingiva with spontaneous bleeding in the maxillary anterior region for a period of one year. The health history documented the use of contraceptives for one year, and a clinical examination revealed the existence of poor oral hygiene and enlarged painful gingival tissues that bleed when touched.This case reaffirms the fact plaque control is the most important procedure in any periodontal therapy. Another factor contributing to the excellent response to therapy is patient compliance. The patient followed home care instructions well and was effective in personal oral hygiene measures.